História de trabalhadores e do trabalho na fronteira Brasil-Paraguai (1960-2015) - Fiorotti, Cíntia (2015)
This research has the purpose of problematizing the history of the work and the workers in the confluence region of the borders of Salto del Guairá/Paraguay, Guaíra and Mundo Novo/Brazil in the period of 1960 to 2015. In order to that, we analyzed the relations between the processes of construction and assimilation of the definition of what would be the border, the criminalization of the social practices and the organization of the working worlds in the region. Through the analysis of oral and documental sources, we reflected about the changes in the living and working in the border and verified that these changes are not only reduced to modifications in the law and economy, but also in the historical meanings attributed to the border itself.